The Influence of Transformational Leadership on Psychological Well-Being Assessing The Moderating Role of Workplace Spirituality - Yuliyasti, Rahmi; Fahmy, Rahmi; Syahrul, Laura; Yulihasri, Yulihasri (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
Minangkabau women are considered bundo kanduang who always maintain the integrity of the family in West Sumatra. Minang women realize that helping their husbands is a very noble thing and does not conflict with cultural values. The favorite profession chosen by many women in Minangkabau is lecturer. If observed from LLDIKTI X data, the number of female lecturers is greater than male lecturers, but in terms of rank, male lecturers are better than female lecturers. For women, working to help their husbands is something noble and can improve their psychological well-being. This study aims to prove and analyze the influence of transformational leadership on psychological well-being through workplace spirituality as a mediating variable in female lecturers at a number of leading universities in Padang City. The analysis method used is quantitative, namely through Structural Equation Modeling (SEM) analysis which is processed using Partial Least Square or PLS software.The results of the hypothesis testing found that transformational leadership and workplace spirituality have a positive and significant effect on the psychological well-being of female lecturers, then in the indirect effect test it can be proven that workplace spirituality is able to moderated the relationship between transformational leadership and the psychological well-being of female lecturers at a number of leading universities in Padang City. Result of the testing founding transformational leadership and workplace spirituality are able to improve the psychological well-being of female lecturers, in addition through workplace spirituality, the implementation of a transformational leadership style by the head of the institution is able to encourage the realization of psychological well-being in female lecturers.